Spirit Tauhid dalam Kurikulum Merdeka: Telaah Pemikiran Ismail Raji Al-Faruqi - Aldi Prasetyo; Supriyanto Supriyanto; Suliwati Suliwati (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
Violations of human values still occur in various regions in Indonesia.  Indonesia needs to reflect on religious values that encourage humans to an ideal social system. Efforts that can be made to realize the ideal social system are through education. One of the important aspects of national education aims to form Indonesian people with a Tawhid spirit. The national education orientation is in line with the scientific development of Ismail Raji Al-Faruqi. To realize the purpose of national education, national education requires a curriculum that is based on the value of Tawhid. Therefore, the Merdeka curriculum that is being massively campaigned must be studied the dimensions of Tawhid contained in it. This study aims to analyze the concept of Tawhid Ismail Raji Al-Faruqi in the Merdeka curriculum to support the achievement of national education goals. This research is literature research. The data collection method uses documentation methods and its data analysis techniques use content analysis. The results of this study show that the Merdeka curriculum has a positive relationship with the thoughts of Ismail Raji Al-Faruqi related to his thoughts on Tawhid. The relationship is reviewed based on the spirit of Tawhid contained in the profile of Pancasila students and the concept of independent learning. Tawhid is understood as the main value that becomes a universal value. That is, the value of Tawhid has implications for all elements of life. Meanwhile, independent learning can be understood as an opportunity for educators to teach faith strengthening.